Examining the Intersection Between Suicidal Behaviors and Intimate Partner Violence Among a Sample of Males Receiving Services From the Veterans Health Administration. (September 2014) - Cerulli, Catherine; Stephens, Brady; Bossarte, Robert
Veterans comprise 10% of the population, and suicide among Veterans has garnered national media and policy attention. Existing research suggests that intimate partner violence (IPV) is a risk factor for suicidal behaviors among some high-risk populations. This report offers a new perspective: the intersection between Veterans' suicidal thoughts and IPV, both victimization and perpetration. The data were obtained from a northeast telephone survey of Veterans ( n = 296) using Veterans Health Administration services and yielded a 27% participation rate. Findings suggest male Veterans who are IPV involved have increased odds of suicidal thoughts and behaviors.